Promotional digital marketing strategies with social networks: Bibliometric analysis of digital strategies through Facebook and Instagram - Marín Palacios, Cristina; Botey Fullat, María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Promotional strategies have an increasing impact on sales, being strongly transformed with the debelopment of social networks. This study is to provide a bibliometric analysis of promotional marketing strategies highlighting the new associated social networks. It is made on a selection of Scopus articles (with VOSviewer, words: marketing, promotion, Facebook or Instagram) obtaining 271 publications (2008 to 2022). A strategy shift towards data mining and machine learning is detected in Instagram. This study concludes with insights that can help managers to drive marketing strategies in their companies.